Hardware and Software: Verification and Testing 11th International Haifa Verification Conference, HVC 2015, Haifa, Israel, November 17-19, 2015, Proceedings - Piterman, Nir.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 11th International Haifa Verification Conference, HVC 2015, held in Haifa, Israel, in November 2015. The 17 revised full papers and 4 invited talks presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on hybrid systems; tools; verification of robotics; symbolic execution; model checking; timed systems; SAT solving; multi domain verification; and synthesis.
Keywords: Software engineering; Computer logic; Programming languages (Electronic computers).; Mathematical logic; Artificial intelligence; Computer communication systems; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages; Artificial Intelligence; Computer Communication Networks